Enlarged accessory spleen after splenectomy mimicking a pancreas tumor. (January 2021) - Tuan Linh, Le; Tra My, Thieu-Thi; Van Lenh, Bui; Giang, Tran-Van; Viet Bang, Luong; Duc, Nguyen Minh
Highlights: Enlarged accessory spleens are often misdiagnosed as neoplasms. Imaging features and histopathology of accessory and normal spleens are similar. Accessory spleen should be considered in differential diagnosis of abdominal tumors. Abstract: Introduction: An accessory spleen (AS), a common condition, is usually located in the hilar region of the spleen. ASs are not often large; however, after splenectomy, the initially inactive AS may become reactive and hypertrophic. Therefore, an AS can be misdiagnosed as a neoplastic tumor and removed unnecessarily. An undiagnosed abdominal mass located in the spleen site in a patient who has had a splenectomy must be managed carefully. Computed tomography (CT) scanning and magnetic resonance imaging (MRI) may provide useful information for the diagnosis, preventing unnecessary surgery. Case presentation: Herein, we report the case of a 38-year-old female with an enlargement of AS after splenectomy that was misdiagnosed as a primary tumor of the pancreas and managed by a nonessential surgery. Conclusion: An AS should be added to the differential diagnosis of a pancreatic tail tumor for patients with prior splenectomy in order to avoid nonessential surgery to ensure the patient's safety.